Genetic contributions to brain criticality and its relationship with human cognitive functions - Yumeng Xin; Yue Cui; Shan Yu; Ning Liu (Proceedings of the National Academy of Sciences, 2025)
Recently, extensive evidence has demonstrated that the brain operates close to a critical state, characterized by dynamic patterns known as neuronal avalanches. The critical state, reflecting the delicate balance between neural excitation and inhibition, offers numerous advantages in information processing. However, the role of genetics in shaping brain criticality is not fully understood. Whether there is any shared genetic factor influencing the critical state and cognitive functions remains elusive. Here, we aimed to address these questions by examining the heritability of brain criticality and its relation to cognitive function by analyzing resting-state functional magnetic resonance imaging (rs-fMRI) in 250 monozygotic twins, 142 dizygotic twins, and 437 Not-twin subjects. We found that genetic factors substantially influenced brain criticality across various scales, encompassing brain regions, functional networks, and the whole brain. These genetic influences exhibited heterogeneity, with the criticality of the primary sensory cortex being more strongly influenced by genetic factors compared to that of the association cortex. Furthermore, we combined rs-fMRI data with transcriptional microarray data from the Allen Brain Atlas: Human Brain (ABHB) dataset and found that the organization of regional critical dynamics was highly explained by a specific gene expression profile. Finally, our results showed that the critical state was correlated with total cognition and had a genetic link with it. These findings provide empirical evidence that brain criticality is a biological phenotype and suggest a shared genetic foundation underlying brain criticality and cognitive functions. Our results pave the way toward revealing specific biological mechanisms contributing to critical dynamics and their associations with brain function and dysfunction.